2006
DOI: 10.1167/iovs.06-0567
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-Specific Proteolysis in Primate Retina: Contribution of Calpains in Cell Death

Abstract: Taken together, these results suggested that calpain activation in primate retinas could play an important role in cell death during hypoxia caused by elevated IOP from glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…In previous studies on rat and primate retinal organotypic cultures, hypoxia (95% N 2 /5% CO 2 without glucose) induced activation of calpains and proteolysis of their substrates, and these effects could be inhibited by a calpainspecific inhibitor (SJA6017), resulting in a prevention of cell death (Tamada et al, 2002;Nakajima et al, 2006). In the present study, RGC-5 cells clearly underwent cell death 24 h after oxygen-glucose deprivation (94% N 2 /1% O 2 /5% CO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on rat and primate retinal organotypic cultures, hypoxia (95% N 2 /5% CO 2 without glucose) induced activation of calpains and proteolysis of their substrates, and these effects could be inhibited by a calpainspecific inhibitor (SJA6017), resulting in a prevention of cell death (Tamada et al, 2002;Nakajima et al, 2006). In the present study, RGC-5 cells clearly underwent cell death 24 h after oxygen-glucose deprivation (94% N 2 /1% O 2 /5% CO 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calpain activity has been shown in models of ocular hypertension, 20 NMDA excitotoxicity, 27 hypoxia, 21,26 and serum withdrawal, 25 and these reports demonstrate a degree of protection from various calpain inhibitors. Our study shows that after calcium influx and serum withdrawal in vitro, calpains are active and calpain inhibition affords protection.…”
Section: Discussionmentioning
confidence: 88%
“…18 Previous studies reported calpain activation in models of retinal cell apoptosis involving ocular hypertension 20 and hypoxia. 21 The purpose of our study was to examine the role of active calpains in RGC apoptosis and to examine the effect of calpain inhibitors. It has been suggested that excitotoxic death plays a role in glaucoma and is caused by glutamate-mediated calcium influx and that this death could be mimicked using the calcium ionophore A23187.…”
mentioning
confidence: 99%
“…Calpain activation and retinal cell death has also been observed in retinitis pigmentosa [17,28]. Retinas from monkeys cultured under hypoxic conditions show increased cell death and leakage of lactate dehydrogenase [29]. Increased calpain expression and accumulation of α-spectrin have also been observed in hypoxic retinas.…”
Section: Introductionmentioning
confidence: 93%
“…In hypoxia there is an increase in calcium influx which may aid proteolysis of calpain specific substrates. Calpain inhibitor SJA6017 reduces the proteolysis of α-spectrinin hypoxic retinas [29]. Experiments performed on hypoxic rat retinas revealed elevated presence of calpain-1 and calpain-2 [30].…”
Section: Introductionmentioning
confidence: 97%